Social Media Versus Students’ Learning Outcomes: Insights from a South-West Nigeria University - Ojo, Olayinka; Opeloye, Bolanle Amudat; Olugbade, Damola (Tauladan Fathimah Azzahra, 2024)
This study investigates the influence of social media on the learning outcomes of undergraduate students at the University of Ibadan, Ilesa campus, South-West Nigeria. Employing a descriptive survey research design, a total of 290 randomly selected undergraduate participants from 200 to 400 levels were included. The research instrument, a self-developed questionnaire titled “Social Media and Students’ Learning Outcomes,” demonstrated good reliability with a Cronbach’s Alpha coefficient of 0.739. Data analysis was conducted using percentage, mean, and ANOVA. The findings indicate that a majority of the participants regarded themselves as moderate to proficient users of social media platforms. Notably, WhatsApp, Facebook, and Instagram emerged as the most favored platforms among university students. Additionally, the study highlights the discernible effects of social media on students’ attitudes, academic performance, and academic interactions. Notably, 99.3% of undergraduates were identified as active social media users. The study concludes that while social media may not inherently enhance students’ attitudes towards learning, its unique features could be strategically leveraged to augment overall learning outcomes. The findings underscore the importance of judiciously incorporating social media as a potential educational tool in the university context. Recommendations are extended to stakeholders for thoughtful consideration when integrating social media into teaching and learning practices.